PENGARUH PENGALAMAN KERJA, BEBAN KERJA DAN TEKANAN WAKTU TERHADAP KEMAMPUAN AUDITOR DALAM MENDETEKSI KECURANGAN (FRAUD) PADA KAP DI PROVINSI BAL - Ni Luh Putu Pradnya Dewi; Putu Aristya Adi Wasita; Eka Putri Suryantari (Universitas Triatma Mulya, 2023)
The aim of this study is to explore the influence of work experience, workload, and time pressure on the auditor's ability to detect fraud. This research was conducted using a quantitative approach by taking locations at the Office of the Public Accountant in the Province of Bali. This study targets a population of 71 auditors. Through the purposive sampling method, there were 37 auditors who met the criteria in this study. Empirical data were collected by distributing questionnaires and analyzed using a multiple linear regression approach. This study succeeded in proving that there is a significant influence of the variables of work experience, workload, and time pressur on the auditor's ability to detect fraud. Work experience is proven to be able to have a positive and significant influence on the auditor's ability to detect fraud by 0.931. Furthermore, the findings revealed that workload and time pressure proved to have a negative and significant effect on the auditor's ability of 0.425 and 0.456. Thus, the auditor is expected to always strive to improve the skills, abilities, and knowledge they have in order to be able to always increase public confidence in their responsibilities